The Impact of ASEAN-Korea Free Trade Agreements on Indonesian Export of Manufacturing Goods - Bernadheta Mia Tri Mareta (ETIKONOMI, 2018)
Along with an attempt to promote the export performance of manufacturing goods, the number of investigation about the potential benefit or harm of free trade agreements is still weak in Indonesia. This paper highlights the effect of ASEAN-Korea Free Trade Agreement (AKFTA) on Indonesian export of manufacturing products since AKFTA as one of the significant initiatives in Southeast Asia is expected to boost Indonesian export. By using augmented gravity models with panel data, this paper investigates the presence of trade creation and trade diversion effects on Indonesian export with 20 trading partners, covering a 26-year period from 1990-2015. Fixed effects with least square dummy variable (LSDV) models are applied to tackle the endogeneity problems of FTA by controlling the unobserved heterogeneity. The results showed that trade diversion outweighs trade creation effects in almost all categories, confirming a decrease in export from member to non-member countries.DOI: 10.15408/etk.v17i2.7342